Application of Waste Plastic Films in Road Infrastructure and Construction - Ki, Dongwon; Kang, Shin Young; Ma, Gyeonghoon; Oh, Han Jin (Frontiers in Sustainability, 2021)
Recycling waste synthetic resins, including rigid and film plastics, is a pressing issue worldwide due to the issues associated with waste treatment. Using products originating only from plastic wastes could be a promising way to improve the waste recycling rate and address plastic consumption. This study presents the applications of waste plastic films (WPFs) in urban infrastructure and construction materials, especially bearing loads. WPF-recycled products (WPF-RPs) were evaluated for mechanical properties, including strength (compressive and tensile), thermal expansion coefficient, accelerated weathering, dynamic stability, and environmental aspects, such as the presence of hazardous substances. Subsequent tests confirmed moderate strength, good weathering stability against solar irradiation, and superior road pavement vehicle load through wheel-tracking tests compared with the standards for asphalt. Additionally, hazardous substances were mostly not detected or were under permissible limits in the composition and leachate contents of WPF-RPs. After using temporary pavement blocks (TPBs) from WPFs at a field site for one month, we conducted slip resistance tests which gave a result of ~33 British pendulum number, indicating the possible application of WPF-RPs in low-speed driving sections, according to the Korean standards of the Ministry of Land, Infrastructure and Transport. Moreover, it was confirmed that fastening structures installed between the TPBs can improve backfilling and compaction defects. This practical research highlights the possible applications of products produced from WPFs for infrastructure development, such as filling materials for burial pipes or tubes; however, these potential aspects should be tested further.